Effect of guselkumab on serum biomarkers in Japanese palmoplantar pustulosis patients in a randomized phase 3 study. Issue 1 (7th December 2022) - Morita, Akimichi; Chen, Yanqing; Leung, Monica W. L.; Kawashima, Naoko; Terui, Tadashi
Abstract: Background: It is reported that treatment of palmoplantar pustulosis (PPP) with guselkumab has greater improvement in clinical responses in terms of palmoplantar pustulosis area severity index (PPPASI) score. Here, we present the effect of guselkumab (100 and 200 mg) on PPP‐related serum proteins and their association with clinical responses. Objectives: To analyze the effects of guselkumab treatment on PPP‐related circulating serum proteins up to Week 72 and evaluate their association with clinical responses. Methods: Serum cytokines (interleukin [IL]‐17A, IL‐17F, IL‐22, tumour necrosis factor‐alpha, interferon‐gamma) and 184 inflammation/immune activation‐related serum proteins were evaluated. Baseline cytokine levels for patients with PPP were compared with healthy controls (HCs) to detect differentially expressed serum proteins using Welch's t ‐test. Correlation with individual PPPASI scores was assessed to explore associations with disease severity. Guselkumab treatment‐associated pharmacodynamic (PD) effects were evaluated as fold changes in cytokine levels compared with baseline. Results: Baseline serum IL‐17A, IL‐17F and IL‐22 levels were elevated in PPP patients ( n  = 159) compared with HCs ( n  = 25) and were significantly correlated with baseline PPPASI disease scores. Serum cytokines were reduced following guselkumab treatment, with maximal reduction at Week 72 for both doses (all p  < 0.01). Lower levels of IL‐17A, IL‐17F and IL‐22 were associated with PPPASI improvement at Week 72. Olink platform analysis identified a decrease in chemokine ligand‐19 and IL‐6 levels with guselkumab compared with placebo. However, the difference between the treatment groups was not significant. The biomarker effect of guselkumab 100 versus 200 mg groups was comparable, suggesting the PD effect is plateaued and higher than 200 mg is unlikely to increase biomarker changes. Conclusions: Targeting IL‐23 with guselkumab in PPP led to a progressive reduction in IL‐17A, IL‐17F and IL‐22 in serum, and lower serum levels of these Th17/Th22 cytokines were associated with better PPPASI response after treatment. Clinical Trials.gov identifier: NCT02641730.